Peranan Guru Dalam Penggunaan Media Pembelajaran Berbasis Information And Communication Technology (ICT) Di SDN RRI Cisalak - Iis Dewi Lestari (Universitas Indraprasta PGRI Jakarta, 2018)
The most important thing in a learning process is the teacher and learning media. Learning media appropriately selected and used by a teacher will certainly have an effect on the learning process and result. The information and Communication Technology (ICT)-based learning media is very important in the development of education. ICT is a program used as a tool for manipulating and conveying information. With ICT, the learning process in the classroom becomes easier because the knowledge and information can be manipulated, manageed and transferred easily. The ICT-based learning media can develop students' thinking skills and professionally improve the ability of teachers. Teachers become more motivated and creative during the class. The purpose of this study is to know the role of teachers in using ITC-based learning media at RRI Cisalak Elementary School. The method used in the research is a qualitative descriptive method. The research conducts in-depth interview, observation and literature review. The samples are taken using a purposive sampling technique. The data are analyzed in some steps, namely data reduction, data presentation, and conclusion. The results of the research show that teachers at SD RRI Cisalak have been able to carry out the learning process by using ICT-based learning media. Teachers play a very big role in the continuity of ICT-based learning. The role of the teacher is also supported by the school principal and school committee by increasing the number of facilities, infrastructures and ICT-based learning media in schools